ASSESSING FISCAL EFFICIENCY, ECONOMY, AND EFFECTIVENESS: A VALUE FOR MONEY STUDY OF REGIONAL GOVERNMENT FINANCE IN BALI - Silviani, Ni Luh Putu Dita (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The Regional Revenue and Expenditure Budget (APBD) plays a crucial role in public financial management at the regional level, influencing development programs and community welfare. However, challenges remain in ensuring budget efficiency and effectiveness. This study analyzes the APBD performance of regencies and cities in Bali Province using the Value for Moneyapproach, focusing on economic, efficiency, and effectiveness aspects. The research employs secondary data from regional financial reports between 2020 and 2023. Findings indicate significant fiscal disparities among regions. Badung Regency demonstrates the highest fiscal independence, with a Local Revenue ratio of 85.73%, while other areas remain highly dependent on central government transfers. Efficiency analysis reveals fluctuating trends, with Gianyar experiencing inefficiency spikes of up to 121% in 2021 before stabilizing in 2023. Badung Regency recorded a high effectiveness ratio of 154% in 2022, reflecting strong fiscal execution but also posing sustainability concerns. Moreover, fiscal balance varies across regions, with some experiencing surpluses while others face deficits, highlighting different budgeting strategies. For instance, Badung reported an expenditure of IDR 7.28 trillion in 2023 against revenues of IDR 7.21 trillion, showing controlled budget management, whereas Bangli faced a deficit with expenditures surpassing revenues. These variations indicate diverse financial strategies and challenges in optimizing budget allocations. This study provides valuable insights for regional governments in enhancing budget efficiency and ensuring fiscal sustainability to support long-term development objectives.